Turbulence Impact on Wind Turbines: Experimental Investigations on a Wind Turbine Model - Al-Abadi, Ali Kedher Kashin; Kim, You-Jin; Ertunc, Özgür; Delgado, Antonio (Journal of Physics: Conference Series, 2016)
Experimental investigations have been conducted by exposing an efficient wind turbine model to different turbulence levels in a wind tunnel. Nearly isotropic turbulence is generated by using two static squared grids: fine and coarse one. In addition, the distance between the wind-turbine and the grid is adjusted. Hence, as the turbulence decays in the flow direction, the wind-turbine is exposed to turbulence with various energy and length scale content. The developments of turbulence scales in the flow direction at various Reynolds numbers and the grid mesh size are measured. Those measurements are conducted with hot-wire anemometry in the absence of the wind-turbine. Detailed measurements and analysis of the upstream and downstream velocities, turbulence intensity and spectrum distributions are done. Performance measurements are conducted with and without turbulence grids and the results are compared. Performance measurements are conducted with an experimental setup that allow measuring of torque, rotational speed from the electrical parameters. The study shows the higher the turbulence level, the higher the power coefficient. This is due to many reasons. First, is the interaction of turbulence scales with the blade surface boundary layer, which in turn delay the stall. Thus, suppressing the boundary layer and preventing it from separation and hence enhancing the aerodynamics characteristics of the blade. In addition, higher turbulence helps in damping the tip vortices. Thus, reduces the tip losses. Adding winglets to the blade tip will reduce the tip vortex. Further investigations of the near and far wake-surrounding intersection are performed to understand the energy exchange and the free stream entrainment that help in retrieving the velocit
UnivIS-Import:2018-02-22:Pub.2016.tech.ITC.stmmec.turbul